Estimated burden of fungal infections in Kenya - John Abuga Guto; Christine C Bii; David W Denning (Journal of Infection in Developing Countries)
Introduction: Kenya is a developing country with a high rate of tuberculosis (TB) and a moderate HIV infection burden. No estimate of the burden of fungal diseases in Kenya is published. Methodology: We used specific populations at risk and fungal infection frequencies from the literature to estimate national incidence or prevalence of serious fungal infections. Used sources were: 2010 WHO TB statistics, Kenya Acquired Immunodeficiency Syndrome (AIDS) Epidemic Update 2012, Kenya Facts and figures 2012, Kenya Demographic and Health Survey 2008-2009. Results: Of Kenya’s population of ~40 million, 43% are under 15 years old and approximately 594,660 Kenyan women get >4 episodes Candida vulvovaginitis annually (2,988/100,000). The HIV/AIDS population at risk of opportunistic infections (OI) is 480,000 and the OI estimates include 306,000 patients with oral thrush (768/100,000), 114,000 with oesophageal candidiasis (286/100,000), 11,900 with cryptococcal meningitis (29/100,000) and 17,000 patients with Pneumocystis pneumonia (42/100,000). Chronic pulmonary aspergillosis following TB has a prevalence of 10,848 cases (32/100,000). The adult asthma prevalence is 3.1% and assuming 2.5% have allergic bronchopulmonary aspergillosis then 17,696 (44/100,000) are affected.  Invasive aspergillosis, candidaemia and Candida peritonitis are probably uncommon. Tinea capitis infects 9.6% of children in Kenya, while fungal keratitis and otomycoses are difficult to estimate. Conclusion: At any one time, about 7% of the Kenyan population suffers from a significant fungal infection, with recurrent vaginitis and tinea capitis accounting for 82% of the infections. These estimates require further epidemiological studies for validation.